DETERMINANTS OF BANK FINANCIAL PERFORMANCE: DEPOSIT FUNDS, POST-EMPLOYMENT BENEFITS, AND INCOME IN INDONESIA - Hasri Zulkarnain; Augustpaosa Nariman (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study aims to analyze the effect of customer deposit funds, post-employment benefit funds, and revenue on the financial performance of banking companies in Indonesia. The research employed a quantitative approach using secondary data obtained from audited financial statements of banking companies listed on the Indonesia Stock Exchange (IDX) for the 2024-2025 period. A purposive sampling technique was applied, resulting in 35 banking companies with a total of 70 firm-year observations. The data were analyzed using multiple linear regression analysis after conducting classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results show that customer deposit funds have no significant effect on financial performance (p = 0.092 > 0.05), indicating that the imbalance between incoming funds and credit distribution hinders profitability. Post-employment benefit funds also have no significant effect on financial performance (p = 0.621 > 0.05), as these funds represent mandatory obligations regulated by law rather than revenue-generating activities. Revenue has a significant positive effect on financial performance (p = 0.013 < 0.05), confirming that interest income from credit distribution is the main driver of bank profitability. The coefficient of determination (adjusted R² = 0.101) indicates that only 10.1% of financial performance variation is explained by the three independent variables. The study concludes that revenue is the primary determinant of banking financial performance, while customer deposit funds and post-employment benefit funds do not significantly influence Return on Assets (ROA). These findings provide practical implications for bank management to focus on revenue optimization and for regulators to monitor credit distribution effectiveness.